Novelties in Peperomia (Piperaceae) from southern Central America - Jiménez, José Esteban; Álvarez-Alcázar, Leonardo; Ramos, Anthony; Flores-Rojas, Jeffrey; Méndez, Miguel (Phytotaxa, 2026)
Peperomia is one of the most diverse genera of flowering plants in the Neotropics. Although several national and regional taxonomic revisions and checklists have addressed the genus in Costa Rica and Panama, important discrepancies and gaps remain. In this study, we describe Peperomia isthmophila, an endemic species from the Central American isthmus that was long confused with Peperomia ebingeri. It can be classified within the morphologically heterogeneous clade Peperomia subg. Micropiper based on its fruits with a subapical stigma, borne on a rounded-conical pseudopedicel, and with the surface uniformly covered by sticky papillae. In addition, we report for the first time seven species for the Costa Rican flora: Peperomia alwynii, Peperomia blanda, Peperomia cocleana, Peperomia erythrospicata, Peperomia hispiduliformis, Peperomia pseudoasarifolia, and Peperomia seemanniana. Peperomia erythrospicata is also newly recorded here for the flora of Panama. Moreover, Peperomia leptophylla, a species that has long been confused with Peperomia galioides, is reported here for both countries. The species Peperomia microphylla is excluded from Mesoamerican flora. Because of the large number of names historically applied to the genus, the limited field documentation of type localities, and the persistence of underexplored regions, Peperomia diversity in Costa Rica and Panama still requires detailed investigation. Morphological descriptions are provided for the new species, along with notes on its affinities, distribution and habitat, phenology, conservation status, etymology, and specimens examined. For the newly recorded species, a discussion of morphologically related species is provided. All taxa are illustrated with live photographs and distribution maps.